Social comparisons on Facebook and offline: The relationship to depressive symptoms - Faranda, M.; Roberts, Lynne (Pergamon Press, 2019)
Facebook and offline social comparisons have been associated with depressive symptoms, however no study has simultaneously examined comparison tendencies across both settings as predictors of depressive symptomology. Accordingly, this study investigated the difference between comparison orientation (tendency to make comparisons) and direction on Facebook and offline, and the predictive utility of these comparisons on depressive symptoms. A convenience sample of 181 young adults aged 18 to 25 years (Mage = 21.90 years, SD = 2.14; 51 males, 130 females) completed an online questionnaire measuring comparisons, depressive symptoms and Facebook use. Paired samples t-tests indicated that participants had higher comparison tendencies offline, CI [1.97, 4.18], d = 0.40, and had more negative comparison tendencies on Facebook, CI [-6.37, -2.58], d = 0.25. Hierarchical multiple regression indicated that offline orientation and negative direction predicted significant unique variance in depressive symptoms (2.6% and 9.4% respectively, f2 = 0.33), whilst Facebook orientation and direction did not. Findings indicate that Facebook comparison tendencies may simply reflect offline comparison tendencies, and that depressive symptoms may be a result of a general tendency to compare across both settings.